IMPLEMENTASI MEDIA PUZZLE UNTUK MENINGKATKAN MOTIVASI BELAJAR KELAS V IPS MIS MODEL PANYABUNGAN - Nur Aida Nasution; Rahmi Seri Hanida; Rica Umrina Lubis (EDU RESEARCH, 2024)
This research is Classrom Action Research using tow cycles, anda each cyecle has 3 meetings. One cycle consists of planning, action, observation, and reflection. The data collection techniques used in this research are observasi, questionnaires, documentation, and the type of research used is quantitative and qualitative research. Based on the results of the research conducted, it can be conluded that use of puzzle learning media can increase the learning motivation of class V students in the research there was an increase in student learning motivation, namely from the results of cycle II which reached an average of 79,73% and The result from cycle I reached an average of 61,66%. Therefore, the increase obtained by researchers from cycles I and II increased 18,07%.